MATHEMATICAL MODEL TO PREDICT THE CAPACITY OF FRESH PRODUCE MARKET - Tetsuya Araki; Tetsuya Koyama; Yasuyuki Sagara; Armansyah H. Tambunan (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT Deregulation policies for the supply chain of agricultural products brought not only a rapid increase in fresh produce that were trensectcd in most of wholesale markets in Indonesia. but also the difficulty in striking an appropriate balance between the expansion of the profit from these transactions and the control of environmental damages in the market as well as surrounding areas, In this study. engineering tieldwork was carried out for totally nine months since 2000, and then a market capacity model has been proposed to predict maximum acceptable amount of incoming products per unit ereaa in the market. The model calculation was based on the standardized unit area in the market. The model was applied to the average amount of daily incoming products to estimate minimal floor space for each product in the market, and then the results indicated that the market capacity should be 15% larger than that in 2003 to solve the overstocks of the products in all the passages of the market. However, it would be difficult to provide sufficient floor space of fresh produce in the market if the number of wholesalers reaches almost the double, as planned by the merket authority, after the completion of the reconstruction project. Therefore, the supply chains should be radically improved to attain the rationalized market in Jakarta, including the abolishment of the regulation related to the status of the market as the only central wholesale market.  Keywords : Engineering  fieldwork, mathematical model, maximum acceptable amount, minimal floor space. supply chain Diterima: 17 Juli 2007; Disetujui: 19 Austus 2007